Pengaruh Rasio Keuangan Dan Karakteristik Pemerintah Provinsi Jawa Timur Tahun Anggaran 2020-2023 Terhadap Financial Distress - Indy Fathimatuz Zahro; Aji Safawalina Marawata; Alfin Nurul Afifah; Felanti Wulandari; Muhammad Tadhi Viki Taurrohman; Malika Safira Salsabila; Mely Septiawati; Usnul Hotimah (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This research aims to evaluate the effect of financial ratios and local government characteristics on Financial Distress conditions in East Java Province during the 2020-2023 budget period. The background of this research is based on the importance of transparency and accountability in local financial management, which has a direct impact on the quality of public services. Financial Distress in this context is defined as the inability of local governments to meet their financial obligations and provide public services according to established standards. This study tests the hypothesis that the effectiveness ratio, efficiency, growth, degree of decentralization, population, and area affect Financial Distress. Using a quantitative approach and secondary data from the financial statements of three districts/cities, the results of the analysis show that all independent variables do not have a significant effect on Financial Distress, as indicated by significance values that exceed 0.05. These results indicate that further studies are needed with broader data coverage and a more in-depth analytical approach to identify factors that affect Financial Distress in the local government sector.